Analisa Kinerja Keuangan Pemerintah Kota Depok Tahun 2019-2022 - Karunia Putri Gustami; Sonny Fransisco; Farah Azzahra Rachmawati; Bunga Fatma Nur (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study was conducted to determine the measurement of the financial performance of the Depok City Government during the 2019-2022 period with value of money measurement indicators using the calculation of three ratios, namely: independence, effectiveness, and efficiency. This research uses descriptive quantitative data analysis method with secondary data processed and obtained from ppid.depok.go.id. The results of this study indicate that Depok City Government finances have a good level of independence, a very effective level of effectiveness but have an inefficient level of efficiency. Financial performance is still inefficient because the amount of expenditure realization is still high and there is no effort to cut expenditure spending each year to improve the efficiency of financial performance.